Brasil e EUA no novo milênio - Lima, Marcos Felipe Pinheiro (Meridiano 47 - Journal of Global Studies, 2011)
Resenha de OLIVEIRA, Marcos Guedes de (Org.). Brasil e EUA no novo milênio. Recife: NEA/Ed. Universitária da UFPE, 2004. ISBN 85-7315-222-2